2019
DOI: 10.3390/nu11071600
|View full text |Cite
|
Sign up to set email alerts
|

More Research Is Necessary to Establish the Ergogenic Effect of Caffeine in Female Athletes

Abstract: Dear Editor-in-Chief, [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…A recent review of the caffeine literature found that only ~13% of the total sample in research on the ergogenic effect of caffeine between 1978 and 2018 were women and that the number of women in studies investigating caffeine effects on speed and muscle power is very low. 9 A likely explanation for this difference in representation of the sexes is that females can be a slightly more challenging cohort to conduct caffeine research on. The use of oral contraceptives 10 and the large variations in hormone concentrations between phases of the menstrual cycles 11 can alter caffeine metabolization speeds, 12 which in turn may alter the ergogenic effects of caffeine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the caffeine literature found that only ~13% of the total sample in research on the ergogenic effect of caffeine between 1978 and 2018 were women and that the number of women in studies investigating caffeine effects on speed and muscle power is very low. 9 A likely explanation for this difference in representation of the sexes is that females can be a slightly more challenging cohort to conduct caffeine research on. The use of oral contraceptives 10 and the large variations in hormone concentrations between phases of the menstrual cycles 11 can alter caffeine metabolization speeds, 12 which in turn may alter the ergogenic effects of caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, variations in strength and power have been demonstrated throughout the menstrual cycle, 13 which can cause noise in performance data and affect overall results. Taken together, although there are a number of studies demonstrating that caffeine clearly has an ergogenic effect in females, 9,[14][15][16] the information about the effect of caffeine on muscle performance in women is uncertain, especially in strength and power performance. As an example, a recent meta-subgroup analysis examined the effects of caffeine on muscle power in females for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, caution would be needed in extrapolating the recommendations made for men to women, since the vast majority of the studies included only male participants [1,2,5,21]. In fact, only ~13% of participants in investigations aimed to determine the ergogenic effect of caffeine are women, while the effect of caffeine in women at high (>9 mg/kg) or very low doses (<1 mg/kg) is unexplored [22]. In addition, due to the menstrual cycle, women are subject to hormonal changes that could affect sports performance [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the research to date typically focuses on the ingestion of 3–8 mg·kg -1 of anhydrous caffeine, rather than the widely available source of caffeine, coffee [5], and predominantly in men [6], with only ten studies comparing men and women [7]. Consequently, there is a lack of research examining the ergogenic effect of caffeine on women [8], and in particular when receiving alternate forms of caffeine delivery, such as coffee [9].…”
Section: Introductionmentioning
confidence: 99%